2007
DOI: 10.1111/j.1468-2982.2007.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

The GRIM2005 Study of Migraine Consultation in France II. Psychological Factors Associated with Treatment Response to Acute Headache Therapy and Satisfaction in Migraine

Abstract: The objective of this analysis was to identify variables associated with treatment response in subjects with migraine. Data were collected from a sample of 10,000 subjects. A battery of questionnaires assessing clinical and psychological variables was completed. Migraine diagnosis was attributed using an algorithm based on the IHS criteria and treatment response using the ANAES criteria. We identified 1534 subjects, of whom 1443 were treated. For 54.2%, at least one ANAES criterion for treatment response was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 24 publications
2
26
1
1
Order By: Relevance
“…The data obtained in the ALMO cohort are consistent with those from previous studies evaluating the effectiveness of almotriptan, such as the Reality with Almogran and Standardized Study with Almotriptan in Early Treatment of Migraine (START) studies 19,20 . The finding that increased patient‐reported treatment satisfaction is associated with better treatment response as determined with the HAS criteria being fulfilled is consistent with similar findings from the GRIM2005 study 16 . This association reinforces the external validity of the VAS for measuring treatment satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…The data obtained in the ALMO cohort are consistent with those from previous studies evaluating the effectiveness of almotriptan, such as the Reality with Almogran and Standardized Study with Almotriptan in Early Treatment of Migraine (START) studies 19,20 . The finding that increased patient‐reported treatment satisfaction is associated with better treatment response as determined with the HAS criteria being fulfilled is consistent with similar findings from the GRIM2005 study 16 . This association reinforces the external validity of the VAS for measuring treatment satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…While the benefits of acceptance coping has been reported in research on asthma [57] and pain [58,59], the relationship is not as clear with migraine. A recent study of acceptance in migraineurs found that greater acceptance of migraine-related pain predicted lower disability/interference with life [60]; however, another study of migraineurs in France showed that dispositional acceptance coping was associated with poorer outcomes [61]. Similarly, dispositional behavioural disengagement was shown to be higher among migraineurs reporting more severe/frequent symptoms [28].…”
Section: Discussionmentioning
confidence: 97%
“…22 Again, a research showed that psychological factors associated with poor treatment response including catastrophizing and the use of maladaptive coping strategies in migraine patients had more averages. 23 Also, during some other investigations it was shown that the use of maladaptive coping strategies can improve the results obtained from the treatment in people with headaches.…”
Section: Discussionmentioning
confidence: 99%